Livestock Feed Production and Utilization: Opportunities, Challenges and the Way Forward - Yeheyis, Likawent (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Training Workshop on Climate Smart Livestock Feed and Forage Innovations. Presentation in Bahir Dar, Ethiopia. May 16th-18th, 2022.